Study on efficiency of players in the volleyball world championship, Italy / Bulgaria 2018 - Cojocaru, A.-M.; Cojocaru, M. (Journal of Sport and Kinetic Movement, 2018)
With every new major competition at the level of the world's top teams, there is progress towards the development of the game, teams always bringing some news that allows them to capture the opponent and climb the hierarchies. These novelties focus mainly on the model of attack and defense play, the content of some gaming actions, the level of efficiency, the peculiarities of specialization on the posts as well as some priorities given to the components of the training. The purpose of the paper is to evaluate, in terms of quantity (weight) and quality (efficiency), the whole content of the actions and the game, as well as the degree of involvement of each player, according to the specialization in positions at the level of the World Volleyball Championship 2018. The research hypothesis assumes that by highlighting the objective tendencies that manifest in the performance of volleyball players in the content and effectiveness of implementation action game, we can define the structure and content of the model of game that can be transferred in training coaches and athletes. The research methods were the bibliographic study, the statistical-mathematical method, the graphic representation method. The possibility of a dynamic approach to the content of the volleyball game is determined by the correct knowledge and understanding of the key aspects of the competitive game in the world, to be transferred and permanently present to the day-to-day concerns of coaches and players. In conclusion, the key aspects of the game result from the actual situations faced by teams and players in an official game whose purpose is winning the game, namely winning sets and points by means of gambling actions that have to pursue a certain high level of effcience, to win the games.